Evaluation of iron overload and adequacy of packed red blood cells transfusion in children with thalassemia major - Shukla, Santosh Kumar; Maurya, Manisha; Shrivastava, Anubha; Mishra, Prakash Chandra (Indian Journal of Child Health, 2019)
Background: Transfusion therapy in patients with thalassemia major needs to address the common questions such as what should be the optimal hemoglobin (Hb) level for effective transfusion and how do transfusion requirements affect the success of iron chelation therapy. Objective: The objective of the study was to evaluate iron overload and adequacy of packed red blood cells (PRBCs) transfusion in children with thalassemia major along with the correlation of serum ferritin level with transfusional iron load and pre?transfusion Hb level. Materials and Methods: This single?center retroprospective observational study was carried out in thalassemia day care center of tertiary care hospital for 1 year over 32 transfusion?dependent ??thalassemic patients up to 18 years of age. Data including pre?transfusion hemoglobin level, number and volume of PRBC transfused, and serum ferritin level for 1 year were analyzed, and annual transfusion iron load was calculated. Correlation of serum ferritin level with transfusional iron load and pre?transfusion Hb level was determined using Pearson coefficient (r) and p-value. Results: The mean pre?transfusion hemoglobin level was 6.4±0.23 g%. The average number and volume of PRBCs transfused in a year were 12.5±3.02 and 112 ml/kg, respectively, with the average annual transfusional iron load of 121.3 mg/kg ±28.9 or 0.3 mg/kg/day. A significant positive (r=0.4184, p=0.017) correlation was observed between serum ferritin level and transfusional iron load with the mean serum ferritin level of 1744±604.6 ng/ml. Negative correlation was observed between serum ferritin and pre?transfusion Hb level (r=?0.2624 and p=0.1537). Conclusion: All patients were undertransfused and this undertransfusion further leads to more accumulation of iron in the body through increased absorption of dietary iron as a result of anemia and ineffective erythropoiesis.